Infill topology optimization of porous structures with discrete variables by the sequential element rejection and admission method. Issue 3 (4th March 2023) - Garaigordobil, Alain; Ansola, Rubén; Querin, Osvaldo M.; Olabarrieta, Ander
Abstract : This article presents an infill topology optimization procedure to generate lightweight porous structures. The proposed method is based on discrete variables and builds upon the sequential element rejection and admission method, extending previous work on topology optimization for infill structures. Local volume constraints are introduced in the conventional formulation of the topology optimization problem for maximum stiffness design instead of the global volume constraint. The local constraints are applied, dividing the interior of a given design shape into quadrangular subdomains with variable aspect ratios. The localized material within these subordinate cells is allowed to flow between two discrete material models, 'real' and 'virtual', where two separate criteria are considered for the rejection and admission of elements. The results demonstrate the effectiveness of the method, showing that detailed porous designs are efficiently achieved with the proposed strategy. Numerical examples demonstrate the effects of the different design parameters.